On the prevalence of communication and English language anxieties as possible antecedents of library anxiety / Janaki Sinnasamy - Sinnasamy, Janaki (2015)
Academic related anxieties are of relevant concern to libraries and librarians because substantial funds are spent annually to provide adequate information resources, services and facilities for students while the optimal use can be hindered by anxieties faced by students. Furthermore, a large portion of the print and electronic resources procured by the libraries are inevitably in the English language. Students in Malaysia who are non-native speakers of English are diversified in their competency of English language. At the University of Malaya, all undergraduates are required to register and pass the Information Skills Course since 1998. The mission is to produce quality graduates who are equipped with the relevant information skills for lifelong learning. Studies however, reveal that the students are more concerned with locating materials listed in their reading lists and favored internet sources, and only then the sources in the library. Why students do not optimize the use of library resources, services, and facilities despite having knowledge of the 'know-hows' of using the library, could be probably be the influence of inherent student related anxieties. The library has to find out if other forms of anxieties inherent in students can have an effect on their behavior and attitude towards the library. The objective of this study is to investigate if the dimensions of foreign language anxiety and communication anxiety can be identified as possible antecedents of library anxiety. The model used is based on the Library Anxiety Expectation Model (LEM). Three sets of instruments used are the Malay translated versions of: (i) Library Anxiety Scale, (Skala Kebimbangan Menggunakan Perpustakaan), (ii) Foreign Language Classroom Anxiety Scale, (Skala Kebimbangan Terhadap Kelas Bahasa Inggeris) and (iii) Personal Report of Communication Apprehension, (Laporan Khendiri Kekhuatiran Komunikasi). A pilot study was carried out on 147 students. The participants for the final study consisted of 114 final year undergraduates at the University of Malaya registered during the first semester of session year 2012/2013. The results of the survey were used to address six research questions and hypotheses. The findings of this study revealed with empirical evidence that the dimensions of foreign language anxiety and communication anxiety are possible antecedents of library anxiety. Students who have inherent communication problems and who have difficulty communicating with others will be unlikely to make full use or demand services from the library. The overall conclusion of this study’s findings infer that the dimensions of communication anxiety as distal antecedents mediate through the dimension Learner Anxiety of English Language anxiety and has an effect on the use of library services and seeking assistance from library staff. Students’ learner anxieties and their fear of communicating with other people and in public or formal situations are also brought into the library scenario. Libraries and librarians should acknowledge that students are anxious to seek assistance from librarians. More enhanced of CMC tools, gentle or non-authoritative methods of answering any queries, whether the query is face-to-face or via email/online, familiarity with culture and ethnic background can be helpful in reducing anxiety.